Hippocampal-Brainstem Connectivity Associated with Vagal Modulation after an Intense Exercise Intervention in Healthy Men - Bär, Karl-Jürgen; Herbsleb, Marco; Schumann, Andy; de la Cruz, Feliberto; Gabriel, Holger W.; Wagner, Gerd (Frontiers in Neuroscience, 2016)
Abstract Regular physical exercise leads increased vagal modulation of the cardiovascular system. A combination of peripheral and central processes has been proposed to underlie this adaptation. However, specific changes in the central autonomic network have not been described in human in more detail. We hypothesized that the anterior hippocampus known to be influenced by regular physical activity might be involved in the development of increased vagal modulation after a 6 weeks high intensity intervention in young healthy men (exercise group: n=17, control group: n=17). In addition to the determination of physical capacity before and after the intervention, we used resting state functional magnetic resonance imaging and synchronic heart rate variability assessment. We detected a significant increase of the power output at the anaerobic threshold of 11.4% (p<0.001), the maximum power output Pmax of 11.2% (p<0.001), and VO2max adjusted for body weight of 4.7% (p<0.001) in the exercise group (EG). Comparing baseline (T0) and post-exercise (T1) values of parasympathetic modulation of the exercise group, we observed a trend for a decrease in heart rate (p<0.06) and a significant increase of vagal modulation as indicated by RMSSD (p<0.026) during resting state. In the whole brain analysis, we found that the connectivity pattern of the right anterior hippocampus (aHC) was specifically altered to the ventromedial anterior cortex, the dorsal striatum and to the dorsal vagal complex (DVC) in the brainstem. Moreover, we only observed a highly significant negative correlation between increased RMSSD after exercise and decreased functional connectivity from the right aHC to DVC) (r=-0.69, p=0.003). This indicates that increased vagal modulation was associated with functional connectivity between aHC and the dorsal vagal complex. In conclusion, our findings suggest that exercise associated changes in anterior hippocampal function might be involved in increased vagal modulation.